The Effectiveness of Kahoot Media in Improving the Quality of Cognitive Evaluation of Grade V Elementary School Students - Hidayanti Fita Anjani; F. Shoufika Hilyana; Imaniar Purbasari (Journal of English Language and Education, 2026)
Conventional assessment methods used in evaluating fifth-grade students at SDN Kedungwaru Kidul 1 have led to low motivation and suboptimal learning outcomes. This study aims to examine the effectiveness of using Kahoot as a medium for evaluating students’ cognitive abilities. A pre-experimental design with a one-group pretest-posttest approach was employed, involving 24 fifth-grade students. Data were collected through multiple-choice tests administered before and after the treatment. The paired sample t-test showed a significant difference between pretest and posttest scores (p = 0.000 0.05), indicating that the use of Kahoot effectively enhances students’ cognitive abilities. Additionally, the implementation of this interactive digital media increased student motivation and engagement during the evaluation process.